Does the Number of Hours Spent on Learning Affect Academic Achievement? - P Rajesh Kumar K Parameswaran Nair, (2021)
Examinations are measurement tools designed to assess learners’ achievement of course learning outcomes. Past studies have shown that factors such as motivation and study time play a part in enhancing learner achievement in assessment. The objective of this exploratory study is to develop a Regression Model that will be used to identify the possible relationship between the learners’ study time with their academic achievement. An online questionnaire survey was administered to 98 respondents of year 1 distance learners of the Principle of Management course in the January 2021 semester at Open University Malaysia. The data on the self-report of study time by the learners for the two variables were analysed. A regression analysis via Statistical Package for Social Sciences (SPSS) analysis tool was performed to study the relationship between the study time (for completing the assignment and preparing for the final examination) and academic achievement. The findings of this study suggest that a regression model can significantly predict academic achievement. However, based on this model, only the study time allocated for completing the assignment appears to be significantly correlated to the course assessment achievement. It is hoped that the findings gathered will lay the foundation for future research that take into consideration other relevant factors associated with study time and academic achievement.